Three‐dimensional whole‐heart T2 mapping at 3T. Issue 3 (19th September 2014) - Ding, Haiyan; Fernandez‐de‐Manuel, Laura; Schär, Michael; Schuleri, Karl H.; Halperin, Henry; He, Le; Zviman, M. Muz; Beinart, Roy; Herzka, Daniel A.
<x xml:space="preserve">Abstract</x> Purpose Detecting variations in myocardial water content with T2 mapping is superior to conventional T2‐weighted MRI since quantification enables direct observation of complicated pathology. Most commonly used T2 mapping techniques are limited in achievable spatial and/or temporal resolution, both of which reduce accuracy due to partial‐volume averaging and misregistration between images. The goal of this study was to validate a novel free breathing T2 mapping sequence that overcomes these limitations. Methods The proposed technique was made insensitive to heart rate variability through the use of a saturation prepulse to reset magnetization every heartbeat. Respiratory navigator‐gated, differentially T2‐weighted volumes were interleaved per heartbeat, guaranteeing registered images and robust voxel‐by‐voxel T2 maps. Free breathing acquisitions removed limits on spatial resolution and allowed short diastolic windows. Accuracy was quantified with simulations and phantoms. Results Homogeneous three‐dimensional (3D) T2 maps were obtained from normal human subjects and swine. Normal human and swine left ventricular T2 values were 42.3 ± 4.0 and 43.5 ± 4.3 ms, respectively. The T2 value for edematous myocardium obtained from a swine model of acute myocardial infarction was 59.1 ± 7.1 ms. Conclusion Free‐breathing accurate 3D T2 mapping is feasible and may be applicable in myocardial assessment in lieu of current clinical black blood, T2‐weighted techniques. Magn Reson Med 74:803–816, 2015. © 2014 Wiley Periodicals, Inc.